HoloDoc: Enabling Mixed Reality Workspaces that Harness Physical and Digital Content - Li, Zhen; Annett, Michelle; Hinckley, Ken; Singh, Karan; Wigdor, Daniel (CHI 2019 Conference on Human Factors in Computing Systems, 2019)
Prior research identified that physical paper documents have many positive attributes, for example natural tangibility and inherent physical flexibility. When documents are presented on digital devices, however, they can provide unique functionality to users, such as the ability to search, view dynamic multimedia content, and make use of indexing. This work explores the fusion of physical and digital paper documents. It first presents the results of a study that probed how users perform document-intensive analytical tasks when both physical and digital versions of documents were available. The study findings then informed the design of HoloDoc, a mixed reality system that augments physical artifacts with rich interaction and dynamic virtual content. Finally, we present the interaction techniques that HoloDoc affords, and the results of a second study that assessed HoloDoc’s utility when working with digital and physical copies of academic articles.